Covid semiotics
1 online resource
Keywords: "This book examines how people around the world have articulated and shaped their experiences of COVID-19 through a sociolinguistic phenomenon known as magical thinking. Using case studies from throughout the world-China, Egypt, Europe, Jordan, Thailand, East Jerusalem, the UK, and the US-this volume looks at how people managed ambiguity and uncertainty, risk, and social isolation by viewing their experiences of the pandemic as other than, or alongside, those presented by voices and images representing scientifically derived knowledge. Each chapter in the volume introduces the reader to a core semiotic concept and shows how it can be used to analyze and unpack a specific signifying practice. In the conclusion, the several concepts from the chapters-ideological positioning, entextualization and recontextualization, double-voicing, discursive grafting, imaging, and contagion-are revisited and synthesized, in order to demonstrate that semiotics is useful not only in ethnographic studies of various "others" and of various "crises," but also in explaining the quotidian experiences of everyday life. Ultimately, this book reveals that COVID-related magical thinking practices are often as "contagious" as the virus they reimagine, spreading through social media and resulting in such social phenomena as viral videos promoting and rejecting public health practices, the first-lockdown stockpiling of toilet paper and hand sanitizer, resistance to public health recommendations, anti-vax rhetoric, and competing interpretations of emerging public health data. This book not only represents cutting-edge research in the field, but it also provides students of anthropology, linguistics, media, and communication with the vocabulary and conceptual framework to understand the human experience of the COVID-19 pandemic"--